Recall and awareness of gambling advertising and sponsorship in sport in the UK: a study of young people and adults - Natalie Djohari; Gavin Weston; Rebecca Cassidy; Martyn Wemyss; Samantha Thomas (BMC, 2019)
Abstract Background The impact of gambling advertisements shown during sporting events on young people is an important public health issue. While extensive research has taken place in Australia, there is still only a limited understanding of this issue in the United Kingdom (UK). Method A mixed methods study was conducted with 71 family groups comprised of 99 young people (8-16 years) and 71 adults recruited at six sites across South London, England (May-July 2018). Interviewer-assisted surveys investigated recall and awareness of sports betting brands using interviews and a magnet placement board activity developed in Australia. Quantitative data were analysed using descriptive statistics, with qualitative data interpreted using thematic analysis techniques. Results Just under half of young people (n = 46, 46%) and more than two thirds of adults (n = 49, 71%) were able, unprompted, to name at least one gambling brand. Boys had a significantly higher recall of brands than girls, as did young people who watched a lot of football on television. Almost two thirds of young people (n = 63, 63%) correctly placed one or more shirt sponsor magnets next to the corresponding football team, and 30% (n = 30) correctly placed three or more sponsors magnets next to the corresponding football team. Just under two thirds of adults (n = 44, 62%) correctly placed one or more shirt sponsors magnets next to the corresponding football team. Young people recalled seeing gambling advertising on television (n = 78), technology/screens (n = 49), and in association with sports teams (n = 43). Adults recalled seeing advertising on television (n = 56), on technology/screens (n = 37), in sports stadiums (n = 34), and in betting venues (n = 34). Over three quarters of young people (n = 74 out of 95 responses, 78%) and 86% of adults (n = 59 out of 69 responses) thought that betting had become a normal part of sport. Conclusion In order to reduce the exposure of young people to gambling advertising, policymakers in the UK should consider comprehensive approaches, similar to those applied in tobacco control, which cover all forms of advertising, including promotion and sponsorship.